Development of Accreditation Acceleration Model We-Based Quality LKP Guarantee In Gresik District East Java Provience - Utomo, Hery Setyo (Universitas Malikussaleh, 2019)
The quality of out-of-school education in Indonesia varies greatly and varies in quality . Efforts to improve the quality of national education by the government are always carried out in stages, planned and measured. To be able to organize quality education, every Education organizer must be accredited by BAN PAUD and PNF. There are still many LKp who are reluctant to submit accreditation requests, so that the quality of LKP also does not meet the expectations of the community and the government. The purpose of this study is to find a model for the acceleration of LKP accreditation development. The method used in this study uses a qualitative research approach, data sources obtained through in-depth interviews, direct observation and documentation. The results of this study are in the form of a product guidance acceleration of LKP accreditation. Accelerating the Development of the Accreditation Model LKP WEB-based quality assurance in Gresik Regency needs a mentoring process by a team of experts in this case the assessors are members of Pokja BAN PAUD and PNF Gresik Regency so that accreditation in Gresik Regency does not run stagnant but can run faster and quota given to the Regency Gresik can be fulfilled.